ANALISIS GENDER PADA UNDANG-UNDANG NO. 1 TAHUN 1974 DAN KOMPILASI HUKUM ISLAM TENTANG HAK-HAK ISTRI - Mustopa Kamal; Saepul Bahri (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
Understanding of gender review review on marriage rights and obligations in Marriage Act No. 1 of 1974 and Compilation of Islamic Law which is still gender biased. Articles relating to the rights and obligations of married couples in the Marriage Act No. 1 of 1974 and the Compilation of Islamic Laws, the dichotomy between public spaces and private spaces which consider them to have very different differences in certain matters which make women so low and illustrates that the ideal woman is a woman who is always hanging, consumptive nature that is always confined in the house. Certainly irrelevant to the condition of the nation that began to develop in a life view.